Implied Volatility Futures Trading Activity and Impacts on Asian Stock Market: An Empirical study - Pham, Duc Nam Trung (2014)
This study analyzes impacts of the adoption of a new type of derivatives instrument in the Asian stock market- the implied volatility futures. Furthermore, the analysis is carried on to the preferences of hedging tools in the two pioneering markets in such adoption, Hong Kong and Japan. Unlike other conventional derivatives, the relationship derivatives on volatility and its underlying assets is almost impossible to be modeled, thus creates several difficulties in pricing as well as researching. This paper however is not focused on the complex aspect of modeling such derivatives but more to the event of the introducing of the trading activity. In particular, this will be at first an event study the issue of futures based on the NIKKEI 225 VI Index in Japan and VHSI Index in Hong Kong which are the Asian version of the famous Chicago Board Options Exchange’s VIX Index. Besides, it will also show a causal analysis of those futures contracts and their underlying Indexes. Therefore, the study will give a more insightful about the relationship between futures trading, structural flow of information and volatility in Asian market.